Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10895-011-0993-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intermolecular Interactions in Solid State Fluorescent Conjugated Polymer Chemosensors

Abstract: A functionalized fluorescent conjugated polymer, tolylterpyridine poly(p-phenyleneethynylene-thienyleneethynylene (ttp-PPETE), was designed and synthesized to detect trace amounts of toxic transition metal pollutants in ground water. Photophysical studies in tetrahydrofuran (THF) successfully demonstrated this polymer as a selective and sensitive chemosensor for Ni(2+) and Co(2+) in aqueous solution. Solid state composites of these chemosensors have now been prepared which can be modified to provide for inexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…The excitation spectrum maximum was at 451 nm, while the fluorescence peak was at 502 nm. The bathochromic shift of excitation and fluorescence maxima compared to those in the toluene solution can be explained by the solid fixation of NI3 into the polymer matrix and the inability to undergo conformational changes [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation spectrum maximum was at 451 nm, while the fluorescence peak was at 502 nm. The bathochromic shift of excitation and fluorescence maxima compared to those in the toluene solution can be explained by the solid fixation of NI3 into the polymer matrix and the inability to undergo conformational changes [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The excitation spectrum maximum was at 451 nm, while the fluorescence peak was at 502 nm. The bathochromic shift of excitation and fluorescence maxima compared to those in the toluene solution can be explained by the solid fixation of NI3 into the polymer matrix and the inability to undergo conformational changes [40,41]. The photophysical characteristics of the poly(St-co-N3) were also examined in the toluene solution, where the copolymer was well soluble and in a thin polymer film (60 µm).…”
Section: Spectral Characteristics Of Ni3 and Ni4mentioning
confidence: 99%
“…In addition, intramolecular and intermolecular interactions exert considerable influences on the properties. 12,13 Higher-order structures of organic materials are dependent on these interactions and molecular shapes. Precise molecular design can lead to desirable, highly-ordered structures for various applications.…”
mentioning
confidence: 99%
“…A more practical approach is to transfer the FCPs from solution to a solid-state matrix, and incorporate them into a field-based chemical sensing device [23][24][25]. Previous studies in the Jones group and others have shown that the photophysical properties of the solid state chemosensors are significantly affected by intermolecular interactions among polymer chains [26]. This phenomenon has been shown to significantly reduce the quantum efficiency of light emitting diodes (LEDs) and sensor devices.…”
Section: Introductionmentioning
confidence: 99%